Associations between maternal body mass index and diet composition with placental DNA methylation at term. (April 2020) - Thakali, Keshari M.; Zhong, Ying; Cleves, Mario; Andres, Aline; Shankar, Kartik
Abstract: Introduction: Maternal obesity and poor quality diets are associated with greater risk of obesity in offspring. Maternal diet and obesity influence placental gene expression and nutrient transport, but the impact of diet and obesity on global epigenetic changes in the placenta are poorly understood. We hypothesized that placental DNA methylation patterns are associated with maternal body mass index (BMI) and/or maternal diet composition. Methods: Using reduced representation bisulfite sequencing (RRBS), we assessed genome scale DNA methylation of 300, 000 CpGs in 150 term placentas from normal weight mothers (n = 72) and overweight/obese mothers (n = 78). Maternal BMI was assessed before week 10 of gestation and maternal diet composition was assessed using 3-day food records at each trimester. Results: In multivariable linear regression models, maternal BMI category (normal weight or overweight/obese), BMI (kg/m 2 ), and maternal saturated fat consumption (g/d) were associated ( p < 0.0001) with methylation of 185, 103, and 302 CpGs, respectively. Of the 56 CpGs associated with both maternal BMI category and maternal BMI (p < 0.0001), GO analysis showed biological processes related to SREBP signaling, phospholipid transport, granulocyte differentiation, and RNA pol II transcription to be affected. Maternal saturated fat intake was associated with methylation of 302 CpGs ( p < 0.0001). These genes were related to chromatin remodeling, IGF receptor, PI3K, and nitric oxide synthase signaling. Discussion: These data suggest that placental DNA methylation status is associated with both maternal obesity and maternal saturated fat intake, possibly contributing to maternal obesity-associated changes in placental function. Highlights: Assessed genome-scale DNA methylation of 300, 000 CpGs in 150 term placentas. Examined if maternal BMI and diet were associated with placental DNA methylation. Maternal BMI was significantly associated with methylation of 185 placental CpGs. Maternal saturated fat consumption was associated with methylation of 302 CpGs. These genes were related to chromatin, IGF receptor, PI3K, and NOS signaling.